Penguatan konsep matematis bagi guru matematika melalui pelatihan software Scilab secara daring - Syamsuri Syamsuri; Hepsi Nindiasari (Universitas Hamzanwadi, 2021)
One of the competencies mathematics teachers need is the deepening of subject matter in mathematical concepts. Among the methods that can be done is through software training to support mathematics lessons. One of the software that can be used in learning mathematics is Scilab software. The use of Scilab software in mathematics learning cannot be separated from the role of the teacher. This service activity aims to carry out online training for Scilab software for learning mathematics. The method used is an online training and evaluation of activities by a questionnaire about knowledge and skills using Scilab software. This online training was carried out synchronously two times in the September 2020 period and was accompanied asynchronously through the Edmodo software. 68 teachers actively participate in this online training who are members of the Mathematics Subject Teachers' Consultation (MGMP) for Lebak Regency High School Mathematics and Nusantara Mathematics for Banten Region. The teacher's response to learning using the Scilab software depends on the teacher's initial ability to use the software. The result of this activity is that this online training can add insight to teachers about mathematics learning software, especially Scilab. Of the 68 participants who participated in the training, only 36 participants filled out the questionnaire. There is 8 person with excellent results, 9 people satisfied, 6 people extraordinary, 10 people enough, and 3 people low.